Less Citation, Less Dissemination: The Case of French Psychoanalysis - Potier, Rémy; Putois, Olivier; Dolez, Charlotte; Jurist, Elliot (Frontiers in Psychology, 2016)
We contribute to inquiries about the visibility of globalized psychoanalytic research in the digital era (cf. Stepansky 2009) by adopting a comparative perspective on a specific geographic area of historical importance for psychoanalysis: France. The largely digital globalized psychoanalytic research field relies on standard bibliometric measures of journal quality (Impact Factor, SJR, etc.), which depend on the number and type of academic cites received by a journal. Thus, citing shapes academic publishing space by differentially valuing its component journals. Conversely, not to cite practically means not to engage with the field. Hence, we took citedness rate as a proxy for global visibility. By drawing on an original database created by one of us, we determined the global citational visibility of French vs. Anglo- American psychoanalytic productions (respective global outreach); and we related it to a first look at French vs. Anglo-American citation practices (geographic breakdown of article cites). We found that, on a 15-year period, the global outreach (citedness rate) of French articles is ten times smaller than that of Anglo- American articles; and that French articles are cited in Anglo-American journals five times more than Anglo-American articles in French journals – which in turn don’t seem to cite their French peers very often. These specific French citation practices could be explained by the implicit modes of reference at work in clinical settings shaped by rich theoretical and clinical local legacies. We conclude by considering that this situation presents French psychoanalytic research with a formidable opportunity for increased citational visibility.